Effect of best bet methane abatement feed on feed intake, digestibility, live weight change, and methane emission in local Menz breed sheep in Ethiopia - Bekele, Wondimagegne; Zegeye, Abiy; Simachew, Addis; Kobayashi, Nobuyuki (Frontiers in Veterinary Science, 2025)
This study continued the in vitro screening of locally available ruminant feedstuffs for optimum nutrient composition and low methane (CH4) production in Ethiopia. The best bet feeds from the in vitro study, hereafter called the test feeds, include dried leaves of Acacia nilotica, Ziziphus spina-christi, and brewery spent grains (BSG). The study involves four treatments: Control, Acacia, BSG, and Ziziphus; each treatment provided an equivalent crude protein and estimated enteric CH4 emissions using Modeling and a Laser CH4 detector (LMD). The experiment was designed as a randomized complete block, using initial weight as the blocking factor for 21 yearling castrated Menz sheep. The study spanned 90 days, and digestibility trials were carried out following a month of the feeding trial. The control group exhibited a significantly (p < 0.001) lower dry matter intake (DMI) compared to the test feed group, which had a higher intake, particularly in the Ziziphus group. However, the Ziziphus group demonstrated significantly (p < 0.01) lower CP digestibility than the other groups. The test diet also led to a significantly (p < 0.001) higher weight gain. Notably, the Ziziphus group demonstrated superior performance in weight change (BWC), final body weight (FBW), and average daily gain (ADG). Similar results were observed for CH4 production (g/day), CH4 yield (g/kg DMI), and CH4 intensity (g CH4/kg ADG) using both CH4 measuring methods. The CH4 emission intensity was significantly (p < 0.04) lower in the test feed groups than in the control group. The control group emitted 808.7 and 825.3 g of CH4, while the Ziziphus group emitted 220 and 265.3 g of CH4 per kg of ADG using the Modeling and LMD methods, respectively. This study indicates that LMD could yield biologically plausible data for sheep. Although the small sample size in the Ziziphus group was a limitation of this study, leaf meals from Ziziphus spina-christi and Acacia nilotica, which are rich in condensed tannins (CTs), have resulted in considerable weight gain and enhanced feed efficiency, thereby making these leaf meals a viable and sustainable feed option for ruminants in Ethiopia.